(untitled) (Journal of Partial Differential Equations, 2023)
Option pricing is a major problem in quantitative finance. The Black-Scholes model proves to be an effective model for the pricing of options. In this paper a computational method known as the modified differential transform method has been employed to obtain the series solution of Black-Scholes equation with boundary conditions for European call and put options paying continuous dividends. The proposed method does not need discretization to find out the solution and thus the computational work is reduced considerably. The results are plotted graphically to establish the accuracy and efficacy of the proposed method.